Characterization of experimental cerebral malaria by volumetric MRI A comparative study across the sexes - Alicia Comino Garcia Muñoz; Oumaima Marfouk; Constance P. Michel; Isabelle Varlet; Emilien Royer; Teodora-Adriana Perles-Barbacaru; Angèle Viola (PLoS ONE, 2025)
Cerebral malaria (CM), a potentially lethal neurological complication of the infection by Plasmodium falciparum, affects mostly the pediatric population under 5 years old in sub-Saharan Africa. This clinical syndrome is characterized on anatomical brain imaging by microhemorrhages, parenchymal lesions and brain edema. Epidemiological studies based on sex or gender are rare and do not allow to draw any conclusions on a possible sexual dimorphism in CM. However, some regional data and genetic studies suggest a possible influence of sex on the susceptibility to this clinical syndrome and complications in surviving patients. The murine model of experimental cerebral malaria (ECM) in mice has proven to be a useful and reliable tool to study the pathogenic mechanisms and possible therapeutical approaches for CM. In this study, we used in vivo magnetic resonance imaging (MRI) to assess the differences linked to sex in the development of experimental CM in C57BL/6J mice infected with the murine parasite Plasmodium berghei ANKA. Our volumetric analysis reveals sex-dependent differences in brain swelling and lesion distribution, particularly microhemorrhages, as well as a regionalization of brain edema in ECM, with swelling-prone structures common to both sexes like the cortex and the pons, and others which show sex-specific alterations like the inferior and superior colliculi or the midbrain. Together, our results indicate that ECM is more severe in male than in female C57Bl/6J mice.